Synthetic Salmonella-type lipid A antigen with high serological specificity. - Kasai, N (1986)
A synthetic compound (compound 516), beta(1-6)-linked D-glucosamine disaccharide 1,4'-bisphosphate, which is acylated by (R)-3-hexadecanoyloxytetradecanoyl, (R)-3-hydroxytetradecanoyl, (R)-3-dodecanoyloxytetradecanoyl, and (R)-3-tetradecanoyloxytetradecanoyl groups at positions 2,3,2', and 3', respectively, exhibited in vitro antigenic reactivity of high specificity comparable to that of free lipid A from Salmonella minnesota R595. This was confirmed by an enzyme-linked immunosorbent assay and an enzyme-linked immunosorbent assay inhibition test with monoclonal and conventional antibodies. The results of comparative analysis performed with several synthetic lipid A analogs as well as three monosaccharide derivatives suggested that the complete structure involving both phosphate groups at the C-1 and C-4' positions and the 3-acyloxyacyl groups at the C-2, C-2', and C-3' positions of the glucosamine disaccharide are required for the expression of the serological specificity of Salmonella-type lipid A. This was deduced from the observations that compound 506, a synthetic Escherichia coli-type lipid A which has the same structure as that of compound 516, except that 3-hydroxytetradecanoyl group is substituted for an acyloxyacyl residue at the C-2 position, exhibited significantly reduced antigenic reactivity as compared with compound 516 and that the replacement by the hydrogen atom of the phosphoryl group at the C-1 position or by 3-hydroxytetradecanoyl or tetradecanoyl groups of acyl residues at the 2, 3, 2', and 3' positions of compound 516 results in a marked reduction of reactivity with monoclonal antibodies 5G and 36G. Similar results were obtained by assays with conventional rabbit antibodies, but the structural difference between compounds 516 and 506 could not be distinguished by these polyclonal antibodies. The results of cross-reactions among synthetic analogs with monoclonal antibodies 161M and 1-9M, which have been confirmed to exhibit different serological specificities from the 5G or 36G antibody, also suggested that the nature and linkage of fatty acyl residues as well as the backbone structure of lipid A play an important role in determining serological specificity of the lipid A molecule.